129k views
2 votes
Write each expression as an equivalent expression with a single logarithm. Assume xx, yy, and zz are positive real

numbers.
ln(x) + 2 ln(y) − 3 ln(z)

User Pedriyoo
by
4.4k points

1 Answer

2 votes

Answer:


\ln(xy^2)/(z^3)

Explanation:

Data provided:

ln(x) + 2 ln(y) − 3 ln(z)

Now,

From the properties of log function,

ln(A) + ln(B) = ln(AB)

n × ln(x) = ln(xⁿ)

and,

ln(A) - ln(B) =
\ln(A)/(B)

applying the properties in the given equation

we get

⇒ ln(x) + 2 ln(y) − 3 ln(z)

or

⇒ ln(x) + ln(y²) - ln(z³) (using n × ln(x) = ln(xⁿ))

or

⇒ ln(xy²) - ln(z³) (using ln(A) + ln(B) = ln(AB) )

or


\ln(xy^2)/(z^3) (using ln(A) - ln(B) =
\ln(A)/(B) )

User Jukzi
by
5.0k points